ANALISIS YURIDIS PENYELESAIAN SENGKETA HAK MILIK DI ATAS TANAH FASILITAS UMUM (STUDI KASUS PUTUSAN NO.20/PDT.G/2013/PN-SBG) - RIYANI ARSYA PUTRI (Ilmu Hukum Prima (IHP), 2022)
Land registration facilitates land title holders easily prove the ownership rights over their land. Despite the good administration of land title, some problems are still found about it. As an instance, a dispute over land title to the land used as a public facility. This problem gets complicated due to the collision between all parties who own land title certificate as the supreme ownership right to land conferred by the government and the right of government to control the country who turns the land into a public facility. The plaintiff in ruling number 20/Pdt.G/2013/PN-SBG sues the defendant for committing a violation of the law by issuing a land title certificate under the defendant’s name to the dispute object. The research problems are about what factors cause issuance of land title certificate to the land used as a public facility as mentioned in the ruling number 20/Pdt.G/2013/PN-SBG, how the judge’s consideration is in sibolga district court ruling number 20/Pdt.G/2013/PN-SBG, and how the legal consequences are for the employs normative juridical method with descriptive analysis, which provides detailed and systematical description about the problems. The results of this research demonstrate that two certificates of land title to different persons can be issued due to the land registration officers’ dishonesty and frequent neglect to the provisions requering the owners of land direcly adjacent to the land that is measured to witness the measurement and/or results of the measurement. The ground of judge’s consideration in the hearing of this case is the lawsuit filed by plaintiff stating that defendant has committed and unlawful act; thus, the judge declares that the land title certificate under the name of defendant I is null and void because of overlapping issuance of land title, and that the action committed by defendant I is considered a violation of the law. In additon, the land title certificate held by the defendant is declared to be legally and administratively defective in its registration, so that it is declared to be null and void by the panel of judges.